2021
DOI: 10.1108/jsbed-12-2020-0440
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education in Brazil: Brazilian and Scottish approaches to policy and provision in vocational education

Abstract: PurposeThis paper examines entrepreneurship education (EE) in Brazil and Scotland and unpacks convergent and divergent practices in vocational education (VE). The authors evaluate access to EE in VE and suggest and how it might be advanced in Brazil.Design/methodology/approachThe authors conducted an interpretative phenomenological analysis (IPA); interpretative analysis of interviewee experiences with 12 educationalists, in management and academic roles, from two Brazilian and two Scottish VE institutions, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
(114 reference statements)
0
3
0
1
Order By: Relevance
“…A AFI é uma abordagem metodológica qualitativa essencialmente indutiva, comprometida com a investigação sobre como as pessoas dão sentido e significado as suas experiências de vida (RAJASINGHE, 2020) .2023.v.11.n.28.642 pesquisas na área de gestão, negócios e empreendedorismo tenha se expandido significativamente pelo mundo (WILLIAMS et al, 2021), ainda é subutilizada em países como o Brasil (STADLER; ALBERTON;SMITH, 2022). As pesquisas sobre as percepções de experiências situadas em fenômenos específicos podem se beneficiar da AFI, como método e estratégia de análise dos dados nos estudos aplicados as organizações em seus diversos contextos.…”
Section: Fundamentos Filosóficos Da Afiunclassified
“…A AFI é uma abordagem metodológica qualitativa essencialmente indutiva, comprometida com a investigação sobre como as pessoas dão sentido e significado as suas experiências de vida (RAJASINGHE, 2020) .2023.v.11.n.28.642 pesquisas na área de gestão, negócios e empreendedorismo tenha se expandido significativamente pelo mundo (WILLIAMS et al, 2021), ainda é subutilizada em países como o Brasil (STADLER; ALBERTON;SMITH, 2022). As pesquisas sobre as percepções de experiências situadas em fenômenos específicos podem se beneficiar da AFI, como método e estratégia de análise dos dados nos estudos aplicados as organizações em seus diversos contextos.…”
Section: Fundamentos Filosóficos Da Afiunclassified
“…Researchers have investigated the efficacy of numerous efforts, such as financial aid programs, tax breaks, and regulatory changes [55,56]. They have also considered the significance of establishing networks and collaborations among SMEs, universities, and other stakeholders in order to foster innovation and knowledge-sharing [57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Shi, H argues that nowadays, the demand of enterprises for talent has changed significantly, and education institutions should continuously adjust and optimize the strategy of vocational education in order to cultivate talents adapted to the needs of enterprises [9]. Stadler, A et al found through analyzing Entrepreneurship Education (EE) and Vocational Education (VE) in Brazil and Scotland that the governmental policies, corporate partner support and school knowledge provide a greenhouse for the three parties to build an entrepreneurial ecosystem [10]. Zhang, Q et al evaluated the integration of industry and education in three economic development zones through the correlation entropy complex meta (CECME) model and the coupling degree of coordination (CCD) model, and they found that the degree of integration of industry and education is positively correlated with the high-quality development of the regional economy.…”
Section: Introductionmentioning
confidence: 99%